Nordisk idrottspolitik i brytningstid - Kritiska reflektioner från en svensk lokal horisont - Sjöblom, Paul (Forum for Idræt, 2007)
Artiklen omhandler den nordiske idrætspolitik og hvordan den påvirker idrætsforeningerne, med udgangspunkt i Sverige. Paul Sjöblom: Nordic sport politics in times of unrest – critical reflections from a Swedish horizon The general marketing and plurality processes regarding the Nordic welfare states give evidence to a more multiplex but at the same time also a more specialized, politicized and, therefore, antagonized field of sports. At the same time as parts of the sports movement are being professionalized and commercialized even far down the leagues, new politics of sports get its shape; politics with earmarked means for previously neglected groups. Or at least it does so theoretically. What, in reality, the consequences will be, and what effects this will have upon the actions of the municipalities, we do not know for sure. My studies indicate that the structures of the local communities that are acting in favor of organized, result-oriented, competitive sports are extremely tenacious. Previously established principles of distribution of means were mainly stable during the beginning of the 20th century, even though the heads of the sports movement as well as the heads of central and municipal government speak of »sports for everybody«.